Mexican Americans & the law : el pueblo unido jamás será vencido! - Anaya Valencia, Reynaldo (Mexican American experience., 2004)
"Mexican Americans and the Law illustrates how Mexican Americans have played crucial roles in mounting legal challenges regarding issues that directly affect their political, educational, and socioeconomic status." "With coverage as timely as the 2003 Supreme Court decision on affirmative action, Mexican Americans and the Law offers invaluable insight into legal issues that have impacted Mexican Americans, other Latinos, other racial minorities, and all Americans."--Jacket